Activity of Prosecutor's Offices in The Republic of Turkestan (1922-1924) - ogli, Jaynarov Obidjon Khamid (European Journal of Life Safety and Stability (2660-9630), 2022)
The article covers a wide range of primary sources, such as the organization of the activities of the State Prosecutor’s office in the Turkestan ASSR, the work done by the prosecutor’s office, the issue of personnel in the system, their social status.